176k views
14 votes
Step by step explanation:

12b - b =77

User Seveibar
by
4.5k points

2 Answers

8 votes
Answer:

Simplifying
12b + -1b = 77

Combine like terms: 12b + -1b = 11b
11b = 77

Solving
11b = 77

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Divide each side by '11'.
b = 7

Simplifying
b = 7

God bless you and Have a beautiful blessed day!
User Sammy Ongaya
by
4.4k points
8 votes

Answer:

7

Explanation:

12b -b = 11b

11b = 77

Divide both sides by 11

b = 7

User Iraklii
by
5.2k points